Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Community structure and residence time of fishes associated with select soft coral taxa in Anda, Pangasinan, northwestern Philippines - Romina Therese S. Lim; Cleto L. Nañola; Maria Vanessa Baria-Rodriguez (Aquatic Ecology, 2026)

Encapsulation of tyrosinase in liposomes: A biomimetic approach to efficient biodetection of polyphenols in grape juice - Priscila Alessio; Cibely S. Martin; Mateus D. Maximino; Matheus S. Pereira; Constantin Apetrei; Maria L. Rodriguez-Mendez (Journal of Food Engineering, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Human Footprint Halves Tail Loss Rates in Geckos Worldwide - Lucas Rodriguez Forti; Ana Marta Pereira R. da S. Passetti; Gabriela Fonseca; Maria Eduarda Lima‐Alves; Jandson Lucas Camelo da Silva; Marcus Dantas; Marcelo Henrique Torres de Medeiros; Luís Gustavo de Oliveira Santos; Marcos S. L. Figueiredo; Judit K. Szabo (Global Ecology and Biogeography, 2025)
Aim Anthropogenic changes alter predator–prey systems worldwide. Defensive behaviour is shaped by the costs and benefits for individuals, and we hypothesise that tail shedding, as an escape strategy, has a higher cost for animals in human‐modified environments compared to natural landscapes. Therefore, our central objective was to evaluate the effects of human footprint on the observed frequency of caudal autotomy in geckos. Location Global. Time Period 1964–2023. Major Taxa Studied Lizards. Methods We classified caudal condition as intact, amputated and regenerated in over 140,000 images of 1264 gecko species in the citizen science platform iNaturalist. We included a quantification of tail abnormalities and tested the effects of the Human Footprint Index, body size, habitat preference, and climate variables on autotomy and regeneration rate using two beta‐binomial models. We also reviewed records of caudal autotomy in the literature, searching for relevant articles published in the Web of Science, Scopus and Scientific Electronic Online databases. Results We identified 14,382 cases of shed or regenerated tail in 748 species among iNaturalist observations. For 631 of these species, autotomy has not yet been described in the scientific literature. We observed caudal abnormalities in 36 species. Tail loss rates dropped from approximately 25% to less than 12% in areas with the highest Human Footprint Index, indicating a strong spatial association between anthropogenic pressure and reduced autotomy. Saxicolous and smaller geckos, independently of phylogeny, had a higher rate of tail loss. Main Conclusions We found that gecko tail loss dropped > 50% in areas with high human impact. Despite the increasing number of observations, rates of caudal autotomy decreased from 13.3% in 2000–2011 to 9.7% in 2012–2023, suggesting a trend that could be related to changes in predation pressure or the potential loss of autotomy among geckos under increased anthropogenic landscape transformation.

Evaluating Ecological Restoration Through Natural Regeneration Requires Replicated Landscape‐Scale Monitoring Studies - Michiel van Breugel; Maria Elizabeth Rodriguez‐Ronderos; Jefferson S. Hall; Daisy Dent; Dylan Craven (Global Change Biology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Biomechanical and Compositional Changes in the Murine Uterus with Age - Mari J. E. Domingo; Triniti N. Vanoven; Raffaella De Vita; Maria E. Florian Rodriguez; Kristin S. Miller; Isaac J. Pence (Annals of Biomedical Engineering, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Unveiling the biogas potential of raw Agave leaf juice: Exploring a novel biomass source - Maiki S. de Paula; Oscar F. Herrera Adarme; Maria Paula C. Volpi; Carla I. Flores-Rodriguez; Marcelo F. Carazzolle; Gustavo Mockaitis; Gonçalo A.G. Pereira (Biomass and Bioenergy, 2025)

Characterization of coral communities in the shallow hydrothermal vents of Mabini, Batangas, Philippines - Joana Andrea C. Maningas; Victor S. Ticzon; Maria Vanessa B. Rodriguez (Regional Studies in Marine Science, 2025)

Exploring the effects of cellulose sources on silver reduction and the bacterial removal of nanocellulose-based hydrogel beads - Diego Gomez-Maldonado; Brieanne R. Dickson; Gabriel Au; Michael J. Bortner; Mi Li; Eduardo Espinosa; Alejandro Rodriguez; Brendan Higgins; Maria S. Peresin (Carbohydrate Polymers, 2025)

Unraveling autonomic cardiovascular control complexity during orthostatic stress: Insights from a mathematical model - Martin Miranda Hurtado; Rafael Kaempfer; Justen R. Geddes; Mette S. Olufsen; Maria Rodriguez-Fernandez (Mathematical Biosciences, 2024)

Association of pesticide exposure with respiratory health outcomes and rhinitis in avocado farmworkers from Michoacán, Mexico - Cecilia S. Alcalá; Cynthia Armendáriz-Arnez; Ana M. Mora; Maria G. Rodriguez-Zamora; Asa Bradman; Samuel Fuhrimann; Christian Lindh; María José Rosa (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Genus and size-specific susceptibility of soft corals to 2020 bleaching event in the Philippines - Christine C. Baran; Rhea Mae A. Luciano; Christine S. Segumalian; Darryl Anthony M. Valino; Maria Vanessa Baria-Rodriguez (Marine Biology Research, 2023)

Epimutation in inherited metabolic disorders: the influence of aberrant transcription in adjacent genes - Jean-Louis Guéant; Youssef Siblini; Céline Chéry; Guillaume Schmitt; Rosa-Maria Guéant-Rodriguez; David Coelho; David Watkins; David S. Rosenblatt; Abderrahim Oussalah (Human Genetics, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Enacting boundaries or building bridges? Language and engagement in food-energy-water systems science - Valoree S. Gagnon; Chelsea Schelly; William Lytle; Andrew Kliskey; Virginia H. Dale; Anna-Maria Marshall; Luis F. Rodriguez; Paula Williams; Michael Waasegiizhig Price; Elizabeth A. Redd; Margaret A. Noodin (Socio-Ecological Practice Research, 2022)
Scientific study of issues at the nexus of food–energy–water systems (FEWS) requires grappling with multifaceted, “wicked” problems. FEWS involve interactions occurring directly and indirectly across complex and overlapping spatial and temporal scales; they are also imbued with diverse and sometimes conflicting meanings for the human and more-than-human beings that live within them. In this paper, we consider the role of language in the dynamics of boundary work, recognizing that the language often used in stakeholder and community engagement intended to address FEWS science and decision-making constructs boundaries and limits diverse and inclusive participation. In contrast, some language systems provide opportunities to build bridges rather than boundaries in engagement. Based on our experiences with engagement in FEWS science and with Indigenous knowledges and languages, we consider examples of the role of language in reflecting worldviews, values, practices, and interactions in FEWS science and engagement. We particularly focus on Indigenous knowledges from Anishinaabe and the language of Anishinaabemowin, contrasting languages of boundaries and bridges through concrete examples. These examples are used to unpack the argument of this work, which is that scientific research aiming to engage FEWS issues in working landscapes requires grappling with embedded, practical understandings. This perspective demonstrates the importance of grappling with the role of language in creating boundaries or bridges, while recognizing that training in engagement may not critically reflect on the role of language in limiting diversity and inclusivity in engagement efforts. Leaving this reflexive consideration of language unexamined may unknowingly perpetuate boundaries rather than building bridges, thus limiting the effectiveness of engagement that is intended to address wicked problems in working landscapes.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

Spatial and Short-Term Temporal Patterns of Octocoral Assemblages in the West Philippine Sea - Jue Alef A. Lalas; Romina Therese S. Lim; Joey P. Cabasan; Christine S. Segumalian; Rhea Mae A. Luciano; Darryl Anthony M. Valino; Melchor R. Jacinto; Hazel O. Arceo; Maria Vanessa Baria-Rodriguez (Frontiers in Marine Science, 2022)
Octocorals are relatively understudied than other coral reef organisms despite their ecological and economic values. The Philippines is known to have high marine biodiversity, but information on octocorals is lacking. This study investigated spatial and temporal variations in the assemblage of octocorals in selected reef sites in the West Philippine Sea (WPS)- the Kalayaan Island Group (i.e., Pag-asa, Sabina, Lawak, and Northeast Investigator) and Ulugan in 2017 and 2019. Results showed high octocoral taxonomic richness (at least 10 families) in the study sites. Mean percent octocoral cover in WPS was 5.35% SE ± 0.55, with Sabina having the highest octocoral cover in both years. Significant differences in octocoral cover were observed among sites in both years, but among-station differences were only observed in 2017. Octocoral assemblage also differed among sites in both years (ANOSIM: R > 0.5, p < 0.05), wherein different octocoral taxa dominated in different sites. In particular, variations were driven by high cover of holaxonians, nephtheids, and coelogorgiids in Sabina, and clavulariids, tubiporiids, and xeniids in Northeast Investigator in 2017. In 2019, significant variations were driven by high cover of helioporiids in Pag-asa, while Sabina had higher abundance of holaxonians, nephtheids, alcyoniids, and xeniids. Short-term temporal variation on octocoral cover in monitoring stations in Pag-asa was not observed (Kruskal-Wallis, p > 0.05), although the overall mean octocoral cover increased from 1.23% ± SE 0.47 in 2017 to 2.09% SE ± 0.37 in 2019. Further, there was no significant change in the octocoral assemblage in Pag-asa between years (ANOSIM, R = 0.11, p = 0.07). This study highlights high octocoral taxonomic richness in the WPS relative to other sites in the Indo-Pacific Region and provides baseline information on the octocoral assemblages, which can be useful for future ecological studies and marine biodiversity conservation efforts.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Some like it, some do not: behavioral responses and central processing of olfactory–trigeminal mixture perception - Franziska S. Müschenich; Thorsten Sichtermann; Maria Elisa Di Francesco; Rea Rodriguez-Raecke; Lennart Heim; Marco Singer; Martin Wiesmann; Jessica Freiherr (Brain Structure and Function, 2021)
Exploring the potential of eucalyptol as a masking agent for aversive odors, we found that eucalyptol masks the olfactory but not the trigeminal sensation of ammonia in a previous study. Here, we further investigate the processing of a mixture consisting of eucalyptol and ammonia, two olfactory–trigeminal stimuli. We presented the two pure odors and a mixture thereof to 33 healthy participants. The nostrils were stimulated alternately (monorhinal application). We analyzed the behavioral ratings (intensity and pleasantness) and functional brain images. First, we replicated our previous finding that, within the mixture, the eucalyptol component suppressed the olfactory intensity of the ammonia component. Second, mixture pleasantness was rated differently by participants depending on which component dominated their mixture perception. Approximately half of the volunteers rated the eucalyptol component as more intense and evaluated the mixture as pleasant (pleasant group). The other half rated the ammonia component as more intense and evaluated the mixture as unpleasant (unpleasant group). Third, these individual differences were also found in functional imaging data. Contrasting the mixture either to eucalyptol or to both single odors, neural activation was found in the unpleasant group only. Activation in the anterior insula and SII was interpreted as evidence for an attentional shift towards the potentially threatening mixture component ammonia and for trigeminal enhancement. In addition to insula and SII, further regions of the pain matrix were involved when assessing all participant responses to the mixture. Both a painful sensation and an attentional shift towards the unpleasant mixture component complicates the development of an efficient mask because a pleasant perception is an important requirement for malodor coverage.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Molecular and biochemical basis for the loss of bioluminescence in the dinoflagellate Noctiluca scintillans along the west coast of the U.S.A. - Martha Valiadi; Tristan de Rond; Ana Amorim; John R. Gittins; Chrysoula Gubili; Bradley S. Moore; Maria Debora Iglesias‐Rodriguez; Michael I. Latz (Limnology and Oceanography, 2019)
The globally distributed heterotrophic dinoflagellate Noctiluca scintillans (Macartney) Kofoid & Swezy is well known for its dense blooms and prominent displays of bioluminescence. Intriguingly, along the west coast of the U.S.A., its blooms are not bioluminescent. We investigated the basis for this regional loss of bioluminescence using molecular, cellular, and biochemical analyses of isolates from different geographic regions. Several prominent differences were identified in the nonbioluminescent strains: (1) the fused luciferase and luciferin binding protein gene ( lcf/lbp ) was present but its transcripts were undetectable; (2) lcf/lbp contained multiple potentially deleterious mutations; (3) the substrate luciferin was absent, based on the lack of luciferin blue autofluorescence and the absence of luciferin‐derived metabolites; (4) although the cells possessed scintillons, the organelles that contain the luminescent chemistry, electron microscopy revealed additional scintillon‐like organelles with an atypical internal structure; and (5) cells isolated from the California coast were 43% smaller than bioluminescent cells from the Gulf of Mexico. Phylogenetic analyses based on large subunit rDNA did not show divergence of the nonbioluminescent population in relation to bioluminescent N. scintillans from the Pacific Ocean and Arabian Sea. This study demonstrates that gene silencing and the lack of the luciferin substrate have resulted in the loss of an important dinoflagellate functional trait over large spatial scales in the ocean. As the bioluminescence system of dinoflagellates is well characterized, nonbioluminescent N. scintillans provide an ideal model to explore the evolutionary and ecological mechanisms that lead to intraspecific functional divergence in natural dinoflagellate populations.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Bivalve distribution in hydrographic regions in South America: historical overview and conservation - Daniel Pereira; Maria Cristina Dreher Mansur; Leandro D. S. Duarte; Arthur Schramm de Oliveira; Daniel Mansur Pimpão; Cláudia Tasso Callil; Cristián Ituarte; Esperanza Parada; Santiago Peredo; Gustavo Darrigran; Fabrizio Scarabino; Cristhian Clavijo; et al. (Hydrobiologia, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

Description of a new hydromedusa from the southwestern A tlantic O cean, B ougainvillia pagesi sp. nov. ( C nidaria, H ydrozoa, A nthoathecata) - Miodeli Nogueira; Carolina S. Rodriguez; Hermes Mianzan; Maria A. Haddad; Gabriel Genzano (Marine Ecology, 2013)
A new hydromedusa species of the genus Bougainvillia (Anthoathecata; Bougainvillidae) is described. Bougainvillia pagesi sp. nov. was collected in shallow coastal waters from southern Brazil (~25–26°S) and northern Argentina (~36–38°S). It differs from other species of the genus mainly by two characters: (i) relatively large size (up to ~20 mm wide and high) and (ii) voluminous folded hanging gonads at perradial walls of the manubrium and extending to the proximal region of the radial canals. Its cnidoma is similar to the other species of the genus, with desmonemes (undischarged capsules: 7.08–10.01 × 2.5–5.59 μm) at marginal tentacles and microbasic euryteles (undischarged capsules: 7.66–11.44 × 2.64–4.43 μm) and smaller (undischarged capsules

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)